Spatial, temporal and molecular hierarchies in the link between death, delamination and dorsal closure. - Muliyil, S.; Krishnakumar, P.; Narasimha, M. (Development, 2011)
Dead cells in most epithelia are eliminated by cell extrusion. Here, we explore whether cell delamination in the amnioserosa, a seemingly stochastic event that results in the extrusion of a small fraction of cells and known to provide a force for dorsal closure, is contingent upon the receipt of an apoptotic signal. Through the analysis of mutant combinations and the profiling of apoptotic signals in situ, we establish spatial, temporal and molecular hierarchies in the link between death and delamination. We show that although an apoptotic signal is necessary and sufficient to provide cell-autonomous instructions for delamination, its induction during natural delamination occurs downstream of mitochondrial fragmentation. We further show that apoptotic regulators can influence both delamination and dorsal closure cell non-autonomously, presumably by influencing tissue mechanics. The spatial heterogeneities in delamination frequency and mitochondrial morphology suggest that mechanical stresses may underlie the activation of the apoptotic cascade through their influence on mitochondrial dynamics. Our results document for the first time the temporal propagation of an apoptotic signal in the context of cell behaviours that accomplish morphogenesis during development. They highlight the importance of mitochondrial dynamics and tissue mechanics in its regulation. Together, they provide novel insights into how apoptotic signals can be deployed to pattern tissues.